Engineering polyzwitterion with acylsulfonamide-based betaine structure for protonated switch of surface chemistry at tumoral pH and reductive responsive drug release of polymeric micelles. (September 2020) - Zhou, B.; Cheng, P.; Jiang, J.; Chen, J.; Zhang, L.; Liang, J.; Wu, W.; Meng, Q.; Li, J.
Abstract: The surface chemistry of stimulus-responsive nanoparticles plays an important role in mediating nano-bio interactions in cancer nanomedicine by targeting the unique features of the tumor microenvironment, such as low extracellular pH. To develop therapeutic nanoparticles with high sensitivity and instant response to slight pH differences in the systemic circulation, we produced a novel polyzwitterion with acylsulfonamide-based betaine structure by one-step modification of polycarboxybetaine (PCB) with benzene sulfonamide. The zwitterionic micellar shells show high antifouling in the blood circulation and acutely convert into positive charge via acylsulfonamide protonation, thereby improving cell affinity at tumor sites. Moreover, a disulfide bond between the shell and poly-ε-caprolactone (PCL) core allows for reductive-responsive release of doxorubicin (DOX) after internalization of the polymeric micelles. Finally, in vitro and in vivo competition assays demonstrated that dual responsive drug-loaded micelles have better anticancer efficiency than free DOX or micelles without zwitterionic pH-responsive properties. Thus, we have developed a simple and valuable strategy to enhance pH sensitivity of micellar carriers for cancer treatment. Graphical abstract: Image 1 Highlights: A new polyzwitterion with pH-responsiveness is prepared via one-step carbodiimide chemistry of polycarboxybetaine. Polymeric micelles show highly sensitive, instant and reversible surface chemistry at tumor pHe. Micellar carriers possess excellent antifouling, active cell uptake and redox-responsive intracellular release.